(untitled) (Current Problems in Rail Vehicles, 2025)
The article deals with the benefits of using two-speed gearboxes in individual wheel set drive in regional BEMU vehicles. It analyzes the design possibilities of using a transverse drive in a traction two-axle chassis. It shows the possibilities of energy saving of traction energy achievable with appropriate driving control of a regional BEMU vehicle using an asynchronous or synchronous traction motor and a single-speed or two-speed gearbox.